PERAN KOMPETENSI PROFESIONAL GURU DALAM MENINGKATKAN HASIL BELAJAR AL-QUR’AN HADITS PESERTA DIDIK MI MIFTAHUSSALAM 1 WONOSALAM DEMAK - Alamul Huda,; Subaidi,; Sukarman, (Rihlah Review: Jurnal Pendidikan Islam, 2025)
This study aims to improve the learning outcomes of Al-Qur'an Hadith students through the role of teacher professional competence. The formulation of the problem of this comprehensive paper consists of: 1). What is the role of teacher professional competence in improving the learning outcomes of Al-Qur'an Hadith Students of Madrasah Ibtidaiyah Miftahussalam 1 Wonosalam Demak in the 2024/2025 Academic Year? 2). What are the supporting and inhibiting factors in improving the learning outcomes of Al-Quran Hadith students at Madrasah Ibtidaiyah Miftahussalam 1 Wonosalam Demak in the 2024/2025 Academic Year? 3). How are the results of improving the learning outcomes of Al-Quran Hadith students through the role of professional competence of teachers at Madrasah Ibtidaiyah Miftahussalam 1 Wonosalam Demak in the 2024/2025 Academic Year? This study uses a qualitative approach. This type of research is descriptive qualitative. The object of the research is located at Madrasah Ibtidaiyah Miftahussalam 1 Wonosalam Demak. Data collection techniques through observation, interviews, and documentation. The data obtained were then analyzed using data analysis techniques from Miles and Huberman which consisted of data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that 1) Teachers' professional competence includes: mastering material, conceptual structure, and scientific mindset, mastering competency standards and basic competencies, developing lesson materials, developing their professionalism, utilizing information and communication technology. 2) Supporting factors are a religious environment that has the habit of reciting the Qur'an and is close to religious studies. While the inhibiting factor is the emergence of gadgets that gradually seize children's interest so that they forget the time. 3) The results of improving the learning outcomes of students' Al-Quran Hadith include the cognitive, affective, and psychomotor domains can be improved through the role of professional competence of teachers at Madrasah Ibtidaiyah Miftahussalam 1 Wonosalam Demak in the 2024/2025 Academic Year.